The Effect of ROA, CR, and DER on Company Value in the Consumer Goods Industry, Food and Beverage Packaging Sub-Sector, 2018–2023 Period - Firmansyah, Teguh; Fauzan, Fikran Fakhry; Dhevyanto, Benny; Krisdiana, Krisdiana (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the effect of Return on Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) on company value in the packaged food and beverage subsector on the Indonesia Stock Exchange for the period 2018–2023. Using a quantitative approach and multiple linear regression analysis of 144 panel data observations, the results show that ROA and CR have a positive and significant effect on company value, while DER has no significant effect. The research model explains 79.7% of the variation in company value. These findings emphasize the importance of profitability and liquidity in increasing market valuation, and provide practical implications for management in post-pandemic strategic financial management.